PENGARUH PENGETAHUAN KEUANGAN, SIKAP KEUANGAN DAN KEPRIBADIAN TERHADAP PERILAKU MANAJEMEN KEUANGAN PELAKU UMKM DI MOYO HILIR: Indonesia - Maya Novianti; Abdul Salam (Journal of Management and Business, 2021)
This study aims to test whether financial knowledge, financial attitudes, personality and financial management behavior among MSME actors in Poto Village, Moyo Hilir District. This research uses quantitative methods with primary data. The sample in this study amounted to 100 research subjects obtained by being selected through probability sampling with simple random sampling technique. The data obtained were processed using multiple linear regression analysis tools through SPSS version 16.0 for windows software. The results of the analysis in this study indicate that (1) the variable financial knowledge has a significant effect on financial management behavior among MSME actors in Poto Village, Moyo Hilir District with a value of 4,141> 1,984 (2) the financial attitude variable has a significant effect on financial management behavior among MSME actors in Poto Village, Moyo Hilir Subdistrict, with a value of 3.103> 1.984 (3) the personality variable has a significant influence on financial management behavior in MSME actors in Poto Village, Moyo Hilir District with a value of 0.591 <1.984.